Varistors based on Ta-doped TiO2 - Navale, S. C.; Murugan, A. Vadivel; Ravi, V. (Ceramics International, 2007)
The nonlinear current (I)-voltage (V) characteristics of titanium dioxide are examined when doped with small quantities (0.05-0.5 at.%) of tantalum pentaoxide. For optimum compositions, the nonlinear coefficients are found to be in the range of 25-30 and the breakdown field strength (EB) is similar to 4000 V/cm. The obtained alpha- and E-B-values are higher than the previously reported values for TiO2 ceramics. The acceptor like surface states at the grain boundary adsorb oxygen during sintering and cooling, leading to formation of grain boundary barrier. The grain boundary barrier height (OB) is calculated using Schottky equation. (c) 2005 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Oxides; Schottky barrier; TiO2; varistor

Varistor property of SnO2 center dot CoO center dot Ta2O5 ceramic modified by barium and strontium - Dhage, S. R.; Ravi, V.; Yang, O. B. (Journal of Alloys and Compounds, 2008)
The influence of an alkali earth (Ba/Sr) element in small quantities (< 1 at.%) on non-linear electrical properties of 98.5% SnO2 + 1% CoO + 0.5% Ta2O5 (all in at.%) varistor system has been investigated. The non-linear coefficient increases from 33 to 52 whereas breakdown field strength varies 5025-6050 V cm(-1) for the barium-doped samples. In case of strontium-doped specimens moderate increase in non-linear coefficient but significant increase in breakdown field is observed. It is proposed that due to ionic size misfit, Ba and Sr segregates to grain boundaries thereby modifying their barrier properties. The contribution from grain boundary phase to the electrical property is confirmed by the impedance analysis. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Oxide materials; scanning electron microscopy; Sintering